2001
DOI: 10.1021/cm000938r
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Corrosion Protection Effect in Polyaniline via the Formation of Polyaniline−Clay Nanocomposite Materials

Abstract: A series of nanocomposite materials that consisted of emeraldine base of polyaniline and layered montmorillonite (MMT) clay were prepared by effectively dispersing the inorganic nanolayers of MMT clay in organic polyaniline matrix via in-situ polymerization. Organic aniline monomers were first intercalated into the interlayer regions of organophilic clay hosts and followed by an one-step oxidative polymerization. The as-synthesized polyaniline−clay lamellar nanocomposite materials were characterized by infrare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
249
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 385 publications
(258 citation statements)
references
References 17 publications
7
249
1
1
Order By: Relevance
“…Polymer-clay nanocomposite materials are reported to promote thermal [48,49], mechanical [50], molecular barriers [51], flame retardant behavior [52][53][54][55][56][57][58][59] and corrosion protection properties [60][61][62]. Therefore, the systematic investigation of the reaction possibility of PAA with synthetic C-S-H at low Ca/Si ratio (0.7) as well as to characterize the composite materials by nanotechnological methods are the main interests of this contribution.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer-clay nanocomposite materials are reported to promote thermal [48,49], mechanical [50], molecular barriers [51], flame retardant behavior [52][53][54][55][56][57][58][59] and corrosion protection properties [60][61][62]. Therefore, the systematic investigation of the reaction possibility of PAA with synthetic C-S-H at low Ca/Si ratio (0.7) as well as to characterize the composite materials by nanotechnological methods are the main interests of this contribution.…”
Section: Introductionmentioning
confidence: 99%
“…29 Yeh et al reported that regardless of clay content, the synthesis of PANI/clay nanocomposites with exfoliated silicate layers of clay was realized and they investigated the effect of such nanocomposites on the corrosion protection of cold rolled steel (CRS) when compared with that of an emeraldine base of PANI using a series of electrochemical measurements of corrosion potential and polarization resistance. 30 To our knowledge, however, systematic studies on the effect of structural variation induced by an increase in PANI content on the physical properties of PANI/layered silicate nanocomposites are yet to be done. In the present paper, based on our previous work, 23 we further characterize the structure of PANI/MMT nanocomposites spanning the complete range of PANI content and perform more systematic studies on the effect of structural change on the physical properties, with special emphasis on the electrical properties, of nanocomposites using XRD, transmission electron microscopy (TEM), scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR), electrical conductivity measurements and thermogravimetric analysis (TGA).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that montmorillonite clay and nanosilica can enhance the anticorrosive effect of polymer coatings, owing to the enhancement of barrier properties by increasing the lengths of diffusion pathways for oxygen and water. (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) However, most of the anticorrosive nanocomposite coatings were prepared by incorporating layered montmorillonite clay or nanosilica and should have suitable organo-intercalating or silane-coupling agents to enhance the compatibility between the dispersed phase of inorganic particles and various polymer matrixes. Although there are various organic-inorganic hybrid materials exhibiting excellent corrosion protection, simpler processes or materials for the preparation of nanocomposite coatings are worth developing for mass production.…”
Section: Introductionmentioning
confidence: 99%